PENINGKATAN EFEKTIVITAS PEMBELAJARAN DENGAN PENGUATAN IKLIM SEKOLAH, DAN PENGETAHUAN GURU TENTANG KURIKULUM 2013 - Indri Wulandari; Eka Suhardi (Universitas Pakuan, 2020)
IMPROVING LEARNING EFFECTIVENESS WITH STRENGTHENING SCHOOL ACADEMIC ATMOSPHERE, AND TEACHER KNOWLEDGE ABOUT 2013 CURRICULUMThis study aimed to determine how the learning effectiveness can be improved by examining the relationship between, 1) a school climate by learning effectiveness, 2) knowledge of the teachers about the curriculum 2013 with the effectiveness of learning, 3) the climate of the school and the teacher's knowledge of curriculum 2013 together with the effectiveness of learning. This study used a survey method with the correlational approach undertaken in servant teachers at SMAN Sukabumi. The population in this study amounted to 254 with a sample of 155 people. The collection of data for each variable studied was using questionnaires and tests. The statistical analysis was using regression correlation and partial correlation. The result produced three conclusions: firstly, there was a positive relationship between school climate by learning effectiveness. Secondly, there was a positive relationship between teachers' knowledge of curriculum 2013 with the effectiveness of learning. Thirdly, there was a positive relationship between school climate and teacher's knowledge of the curriculum 2013 together with the effectiveness of learning.